Comparing the diagnostic value of 18F-FDG PET/CT scan and bone marrow biopsy in newly diagnosed pediatric neuroblastoma and ganglioneuroblastoma - Fu, Zheng; Ren, Jiazhong; Zhou, Jing; Shen, Junkang (Frontiers in Oncology, 2022)
Objective This study aims to compare the diagnostic value of 18F-fluorodeoxyglucose (18-FDG) positron emission tomography (PET)/computed tomography (CT) (18F-FDG PET/CT) scan and bone marrow biopsy (BMB) for evaluating bone marrow infiltration (BMI) in newly diagnosed pediatric neuroblastoma (NB) and ganglioneuroblastoma (GNB). Methods We retrospectively reviewed 51 patients with newly diagnosed NB and GNB between June 1, 2019 and May 31, 2022. Each patient had undergone 18F-FDG PET/CT and BMB within 1 week and received no treatment. Clinical data were collected and statistically analyzed, including age, sex, pathologic type, and laboratory parameters. 18F-FDG PET/CT and BMB revealed the result of bone lesions. Results A concordance analysis showed that, in this study population, 18F-FDG PET/CT and BMB were in moderate agreement (Cohen’s Kappa = 0.444; p = 0.001), with an absolute agreement consistency of 72.5% (37 of 51). The analysis of the receiver operating characteristic (ROC) curve determined that the areas under the ROC curve (AUCs) of SUVBM and SUV/HE-SUVmax were 0.971 (95% CI: 0.911–1.000; p < 0.001) and 0.917 (95% CI: 0.715–1.000; p < 0.001) to predict bone–bone marrow involvement (BMI), respectively. Conclusion 18F-FDG PET/CT detects BMI with good diagnostic accuracy and can reduce unnecessary invasive inspections in newly diagnosed pediatric NB and GNB, especially patterns C and D. The analysis of the semi-quantitative uptake of 18F-FDG, including SUVBM and SUVBM/HE-SUVmax, enables an effective differentiation between patterns A and B.